GROWTH OF SEEDLING OF VEGETABLES FERTILIZED WITH DIFFERENT MORPHOLOGICAL PARTS OF THE BLACK MUCUNA - Brandelero, E. M.; Baesso, M. M.; Fabian, A. J.; Modolo, A. J. (Revista Brasileira de Engenharia de Biossistemas, 2016)
In order to improve vegetable horticulture there is a possibility of mineral supplementation of the commercial substrates in order to contribute to the nutrition of these plants. However, the constant irrigations on the trays end up leaching the nutrients, causing the reduction in growth. The objective of this work was to evaluate the growth of seedlings of vegetables subjected to the addition of different morphological parts of the black mucuna. The treatments consisted of the addition of plant residues of leaves, stems and roots of black mucuna cultivated previously and absence of residues, added to the substrate of seedlings production of four species of vegetables (onion, tomato, lettuce and beet), conducted in a design completely randomized with three replicates. It was observed that the addition of leaves of black mucuna contributed to increase the dry matter of the aerial part between 67 and 242% more in relation to the control, and by 32 to 163% more in the height of the plants. However, the addition of the roots of black mucuna reduced the growth of tomato and beet plants, as the stems reduced the beet growth. The leaves of black mucuna added on the seeded trays provided greater nutritional support and, in turn, greater growth of lettuce, tomato and beet seedlings.